The Effect Of Giving Lemon Aroma Therapy On Menstrual Pain For Class Xa Students At MAN 02 Kudus - Winda Yunyaty Harianja; Pintam Ayu Yastirin (LPPM AN NUUR, 2021)
Background: Menstruation is a periodic process that comes every 28030 days. The first menstrual period (menarche) usually begins at the age of 11-15 years. This cycle will continue until menopause, unless pregnancy occurs. Every menstrual period dark colored menstrual blood will be issued every month and lasts 3-8 days. Aroma therapy is a method of relaxation that uses essential oils which in practice are useful for improving one's physical, emotional and spiritual health. This is because therapy using essential oils helps to excite and refresh. The purpose of this study was to determine the effect of giving Lemon Aromatherapy on reducing menstrual pain. Methods: The type of research used is Pre Experiment with the One Group Pretest – Posttest design, which was conducted at MAN 2 Kudus in September 2021 with a sample of 20 students at MAN 2 Kudus. Results: Based on the Wiloxon test, the calculated Z value was 4, 256 with a p-value of 0.000. it can be seen that the p-value <a (0.05), this indicates that there is a significant difference in the intensity of dysmenorrhea pain before and after being given lemon aromatherapy to class XA students at MAN 2 Kudus. Conclusion: There is a change in menstrual pain complaints before and after giving Lemon Aromatherapy